2023
DOI: 10.1177/15396754221139446
|View full text |Cite
|
Sign up to set email alerts
|

How can we implement targeted policies of rumor governance? An empirical study based on survey experiment of COVID-19

Abstract: Since early 2020, COVID-19 has been a major public security crisis that has had an enormous impact on the world. With the spread of the epidemic, rumors occur, some of which have even caused public panic. They have greatly affected the government’s efforts of epidemic prevention and thus urgently need to be evaluated. This study aimed to examine how to make flexible use of different policy tools to govern rumors based on their different characteristics. From the perspective of behavioral public policy, this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…In current practice, rumor management of public health emergencies mainly starts with regulators and media, using traditional means such as deleting posts, dispelling rumors and media guidance ( 8 ). And the public often tends to search for more information to reduce uncertainty in a chaotic environment, which leads to the great spread of rumors ( 10 , 11 ). Numerous studies have indicated the pronounced significance of stakeholder-oriented governance concerning rumors within the domain of public health incidents ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In current practice, rumor management of public health emergencies mainly starts with regulators and media, using traditional means such as deleting posts, dispelling rumors and media guidance ( 8 ). And the public often tends to search for more information to reduce uncertainty in a chaotic environment, which leads to the great spread of rumors ( 10 , 11 ). Numerous studies have indicated the pronounced significance of stakeholder-oriented governance concerning rumors within the domain of public health incidents ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since China is the first country to adopt the new prevention and control measures of "health code" and successfully put them into practice, it is very likely that countries around the world will still face similar problems to China's "health code" in the process of subsequent promotion and application of epidemic prevention and control policies. For example, Jiayi Jiang and Zexing Zheng conducted research on scale development and content analysis of personal information protection and privacy policy compliance in health code App [5]; Dan Zhang and Yunjie Li conducted research and application of Paddle OCR based health code recognition in the context of epidemic prevention and control [6]; Xiaohan Zhang decoding China from the aspects of legal challenges "Covid -19" health code App [7]; Jiaoliang Qin analyzed the collection of personal information and legal checks and balances after the "health code" [8]; Chengzhe Fu, Weijun Huang and Haolin OU conducted an empirical study on how "soft governance" can bridge the "digital divide" in the context of public crisis based on three policy tools [9]; Luyao Wang, Le Wang and Ziqiong Zhang studied the information technology avoidance behavior of the elderly under public health emergencies [10].…”
Section: Research Status Of Health Codementioning
confidence: 99%